Effect of microstructure of modified diatomite on its adsorption properties - T. Ia. Datsko; V. I. Zelentsov (Хімія, фізика та технологія поверхні, 2017)
The effect of microstructural changes caused by chemical modification of diatomite with aluminosilicate nanoparticles on its adsorption properties with respect to fluorine has been elucidated. The surface modification of diatomite with aluminosilicate is accompanied with significant changes in its structure and chemical properties – a growth of specific surface area, a shift of electro-superficial properties and an increase of adsorption capacity for fluorine. Moreover, some kind of synergism takes place after modification: adsorption capacity of aluminosilicate species grafted on the diatomite surface is higher than that of bulk aluminosilicate. The surface-chemical modification of diatomite has been carried out by heating it in a NaOH solution and subsequent treatment with a solution of aluminum salt and after that with ammonia. Amorphous surface silica partially dissolves during the treatment with NaOH and due to addition of an aluminum salt it forms an aluminosilicate compound. The obtained product is further denoted as DMA. The increase in the specific surface area of DMA is connected with variation of the ratio of the micro- and mesopores through the filling of the large mesopores with aluminosilicate and its own microporous structure increment; the specific surface area gets 81.8 m2/g, which is 2.5 times larger than the corresponding value of the initial unprocessed diatomite (37.5 m2/g). Partial substitution of Si atoms in silicates of diatomite surface by Al atoms creates as a result of their different valences an excess negative charge, and pHPZC of the sorbent surface shifts to higher values compared to initial diatomite sample that facilitates the attraction of more negatively charged ions from solution. Both these phenomena lead to that adsorption capacity of modified diatomite (DMA) with respect to fluorine is considerably increased from 10 to 58 mmol/g.